REVIEW OF THE COLLECTIVE MONOGRAPH"ANALYSIS OF RISKS ASSOCIATED WITH FOODIN THE REPUBLIC OF MOLDOVA" - RUDIC, Valeriu; ARÎCU, Aculina (Journal of Social Sciences)
The collective monograph "Analysis of the risks associated with food in the Republic of Moldova" was carried out within the project 20.80009.5107.09 "Improving the quality and safety of food through biotechnology and food engineering" within the State Program (2020-2023), Strategic Priority II "Agriculture sustainable, food security and food safety". The work includes the analysis of the risks associated with improper nutrition, the behavioral characteristics of consumers in relation to the consumption of salt, sugar, sweeteners, trans fats. The risks of contamination of raw materials and food products along the food chain with technogenic pollutants are analyzed in detail: food contamination caused by the environment, contamination caused by animal breeding and care, food contamination during processing, food contamination during transportation and contamination in the result of contact with food packaging.